Review about Weber, Max: Why value judgments should not be made in sociology and economics - Viñao Frago, Antonio (Avances en Supervisión Educativa, 2010)
Title: WHY VALUE JUDGMENTS SHOULD NOT BE DONE IN SOCIOLOGY AND THE ECONOMY Author: Max Weber Publisher: Editorial Alliance ISBN: 9788420649764 Madrid, 2010. Edition, preliminary study, notes and glossary of Joaquín Abellán. As indicated in the back cover of the book, "Why should not value judgments be made in sociology and economics" was published as an article in 1917 by Max Weber (1864-1920) in the journal "Logos" in order to give account and extract the consequences derived from the logical difference between the scope of the verification or explanation of the facts and the assessment of them.